COMPARISON OF BREAST CARE AND OXYTOCIN MASSAGE INTERVENTIONS ON BREAST MILK PRODUCTION IN POSTPARTUM MOTHERS AT THE TANASITOLO HEALTH CENTER, WAJO REGENCY, SOUTH SULAWESI - Mukarrama (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Background: Optimal breast milk production is very important in supporting the success of exclusive breastfeeding in postpartum mothers. Two interventions that are often used to increase breast milk production are breast care and oxytocin massage. This study aims to compare the effectiveness of breast care compared to breast care and oxytocin massage on increasing breast milk production in postpartum mothers at the Tanasitolo Health Center, Wajo Regency, South Sulawesi. Method: This study uses a True experiment design with a posttest equivalent group design approach. The population is all postpartum mothers at the Tanasitolo Health Center. A total sampling technique was used, involving 40 postpartum mothers who were equally divided into a breast care group and a breast care plus oxytocin massage group. The participants were divided into two groups, consisting of 20 individuals in the intervention group and 20 individuals in the control group, assigned randomly. Breast milk production was assessed using the LATCH score, and data were analyzed with the Mann–Whitney test. Results: The study showed that both interventions increased breast milk production, but the average increase in breast milk production in the breast care and oxytocin massage group was higher than the breast care only group, with a p-value of 0.000 (p <0.05). Conclusion: Breast care and Oxytocin massage are more effective than breast care alone in increasing breast milk production in postpartum mothers. It is expected that health workers can provide education and services related to breast care and oxytocin massage as one of the effective interventions in supporting successful lactation in postpartum mothers.